Utilizing FRET-based Biosensors to Measure Cellular Phosphate Levels in Mycorrhizal Roots of Brachypodium distachyon - Shiqi Zhang; Lucas Jurgensen; Maria Harrison (Bio-Protocol)
Arbuscular mycorrhizal (AM) fungi engage in symbiotic relationships with plants, influencing their phosphate (Pi) uptake pathways, metabolism, and root cell physiology. Despite the significant role of Pi, its distribution and response dynamics in mycorrhizal roots remain largely unexplored. While traditional techniques for Pi measurement have shed some light on this, real-time cellular-level monitoring has been a challenge. With the evolution of quantitative imaging with confocal microscopy, particularly the use of genetically encoded fluorescent sensors, live imaging of intracellular Pi concentrations is now achievable. Among these sensors, fluorescence resonance energy transfer (FRET)-based biosensors stand out for their accuracy. In this study, we employ the Pi-specific biosensor (cpFLIPPi-5.3m) targeted to the cytosol or plastids of Brachypodium distachyon plants, enabling us to monitor intracellular Pi dynamics during AM symbiosis. A complementary control sensor, cpFLIPPi-Null, is introduced to monitor non-Pi-specific changes. Leveraging a semi-automated ImageJ macro for sensitized FRET analysis, this method provides a precise and efficient way to determine relative intracellular Pi levels at the level of individual cells or organelles.